The mother lode : a tragicomedy : the space between pleasure and necessity : an exegesis presented in partial fulfilment of the requirements for the postgraduate degree of Master of Fine Arts at Massey University, Wellington - McDonald, Kelly (Massey University, 2019)
This exegesis discusses aspects of my current practice where I make jewellery that melds the narratives of home, workshop and motherhood, to explore power and gender and the subtle and sometimes not so subtle burden they place on women. Drawing on the previous function of objects collected and selected from domestic, industrial and utilitarian realms, these jewellery re-contextualisations traverse tense and complex territories between people, bodies and things. While exploring the material traces of the everyday, they open a space for engagement and debate about womanhood and the emotional labour of parenting.
Keywords: 360602 Fine arts